SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN JASA PENGIRIMAN TERBAIK MENGGUNAKAN AHP-COPRAS - Muhammad Yusan Al Anshari; Setyawan Wibisono (Elkom: Jurnal Elektronika dan Komputer, 2023)
The large number of needs for shipping goods at this time results in freight forwarding service companies having to continue to grow and compete to win the market. Online shop users will also be very confused and have difficulty in choosing a goods delivery service so they consider other factors in choosing a goods delivery service. Starting from prices, ratings, delivery time to the number of branches, online shop users are confused about choosing the best delivery service according to user needs, therefore complete data and an assessment method are needed to find out which delivery service suits the user's wishes. This study aims to develop a decision support system for selecting the best delivery service using AHP-COPRAS with the criteria of price, rating, delivery time and number of branches. the branch will make the delivery service the best choice, this is because the price and rating criteria have the highest weight. On the other hand, shipping services with high prices, small ratings and few branches will be the lowest choice in the ranking list.